Ex-vivo Surgical Repair of a Renal Artery Aneurysm with Kidney Autotransplantation - Sobrinho, Gonçalo (2020)
Renal artery aneurysms are rare. They are most commonly degenerative, congenital or due to medial fibroplasia. Proximal aneurysms can be repaired by endovascular and in-situ surgical techniques. However, aneurysms of the distal renal artery and its branches require ex-vivo surgical repair, also known as auto-transplantation: the kidney is removed, dissected and reconstructed in cold ischemia, and put back in place. A 69-year-old woman, with hypertension, presented with bilateral renal artery aneurysms with a diameter of 3.4 cm on the right kidney and 1 cm on the left kidney. The right renal artery aneurysm, which was due to medial fibroplasia, was successfully repaired using the ex-vivo surgical technique. Patency was confirmed by postoperative computed tomography angiography.